Dual Banking System Perspektif Kaidah Fiqih Maa Haruma Akhduhu Haruma ‘Ithauhu - Dede Abdurohman; Rachmat Syafe’i; Mustafa Mustafa (Ecobankers : Journal of Economy and Banking, 2021)
he birth of the Sharia Business Unit hereinafter referred to as UUS, is a business unit of a conventional bank, so that the existence of UUS capital is supported by conventional banks. Meanwhile, conventional banks use the concept of bank interest. And bank interest in Indonesia as legally as legal is haram, this is based on the fatwa of the Indonesian Ulema Council (MUI) No. 1 of 2004 concerning Flowers. So that UUS business activities begin with bank capital using the concept of interest and from third party (community) capital. These issues will be discussed in the viewpoint of Maa Haruma Akhduhu Haruma „Ithauhu fiqh principles. In this research, the type of research used is descriptive qualitative research. By collecting normative data/literature. The findings of this study are that UUS with its initial status uses conventional bank capital, so the status in using that capital is the same as the status of bank interest, namely usury. This is because UUS receives capital from business with bank interest and on that basis UUS in using it is haram, this is based on the principle of Maa Haruma Akhduhu Haruma „Ithauhu, namely something that is haram to accept, it is also haram to be given. However, if UUS is seen from the point of view of qawaidul khamsah, its legal status will be different. This is because the presence of UUS is the forerunner of the development of Islamic banking in Indonesia. If there are no UUS, the growth and development of Islamic banking in Indonesia are slow. this is included in the realm of ad-dharurat so that kemudharatan allows things that are prohibited Abstrak Kelahiran Unit Usaha Syariah yang selanjutnya disebut UUS merupakan Unit usaha dari bank konvensional, sehingga keberadaannya modal UUS ditopang dari bank konvensional. Sedangkan bank konvensional sendiri menggunakan konsep bunga bank. Dan bunga bank di Indonesia setatus hukumnya ialah haram, hal ini berdasarkan fatwa Majelis Ulama Indonesia (MUI) No. 1 tahun 2004 tentang Bunga. Sehingga aktivitas kegiatan usaha UUS diawali dengan modal bank yang menggunakan konsep bunga serta dari modal pihak ketiga (masyarkat). Permsalahan tersebut akan dibahas dalam sudut pandang kaidah fiqih Maa Haruma Akhduhu Haruma„Ithauhu. Dalam penelitian ini, jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif. Dengan pengumpulan datanya normatif/literatur. Temuan dari penelitian ini ialah UUS dengan status awalnya menggunakan modal bank konvensional maka status dalam penggunaan modal tersebut sama hukumnya dengan status bunga bank yaitu riba. Hal ini dikarenakan UUS menerima modal hasil dari usaha dengan bunga bank dan atas dasar itula UUS dalam menggunakannya haram hal ini didasari atas kaidah Maa Haruma Akhduhu Haruma „Ithauhu yaitu Sesuatu yang haram diterima, haram pula untuk diberikan. Akan tetapi jika UUS dilihat dari sudutpandang qawaidul khamsah akan berbeda status hukumnya. Hal ini dikarenakan hadirnya UUS merupakan cikal bakal perkembangan perbankan syariah di Indonesia. Jika tidak ada UUS pertumbuhan dan perkembangan perbankan syariah di Indonesia lambat. hal tersebut masuk dalam ranah ad-dharurat, sehingga kemudharatan itu membolehkan hal-hal yang dilarang